ICAR–CTCRI Six decades of innovation and service in the tropical tuber crops sector - Byju, G (Indian Horticulture, 2025)
Since its establishment in 1963, the ICAR–Central Tuber Crops Research Institute (CTCRI), headquartered at Thiruvananthapuram with a regional station in Bhubaneswar, has spearheaded research, innovation, and development in tropical tuber crops. Over six decades, ICAR-CTCRI has transformed cassava, sweet potato, elephant foot yam, yams, taro, and a few other crops from underutilized crops into vital contributors to India’s food, nutrition, and livelihood security. The institute has conserved over 5,000 germplasm accessions, released 77 improved varieties, and developed biofortified crops to combat micronutrient malnutrition. It has pioneered climate-smart production practices, IoT-enabled smart farming, pests and disease management strategies, and quality seed systems. Value addition technologies, industrial linkages, and start-up incubation have generated livelihoods, with women and youth empowered through tuber-based enterprises. Farmer participatory research, training, and collaborations strengthened outreach across India. Today, ICAR-CTCRI stands as a global leader in tuber crop science, driving food security, health, and rural prosperity, while shaping a sustainable agro-industrial future.